Students’ Difficulties in English Writing at Eigth Grade of SMP Negeri 2 Tinada - Pakpak Bharat North Sumatera - Sondang Manik; Rony A Sembiring; Bimbi Izumi Sembiring; Oristia G Pakpahan; Torang Sinurat (South Sulawesi Education Development (SSED), 2024)
This research discussed about students’ difficulties in writing recount text at eighth grade of SMP Negeri 2 Satu AtapTinada - Pakpak Bharat north Sumatra. The problem of this research were the students’ difficulties in writing recount text and factors that cause students’ difficulties in writing recount. The objective of this research was to find out the students’ difficulties in writing recount text and to describe the factors that make students have difficulties writing recount text. This research was qualitative descriptive. The source of the data of this research was eighth grade of SMP Negeri 2 Satu Atap Tinada - Pakpak Bharat north Sumatra.. Total of the were 20 students. The researcher used test and gave a questionnaire as the instruments. The researcher analysed the data by editing the data, reducing the data, tabulating the data and the last taking conclusion. The researcher found some facts in the field. First, it was found that the answer that students’ difficulties in writing recount text were difficulties in developing the content, organization, vocabulary, language, and mechanics. The data were got from students’ test that had been analysed. Beside that, the causes of the students’ difficulties in writing recount text were grammatical weakness, knowledge and understanding, less practice, and educational background